2018
DOI: 10.1002/ana.25227
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke in cancer patients: A review of an underappreciated pathology

Abstract: Currently 1 in 10 patients with ischemic stroke have comorbid cancer, and this frequency is expected to increase with continued advances in cancer therapeutics prolonging median survival. Well known for its association with venous thrombosis, cancer has recently emerged as a significant risk factor for arterial thromboembolism, including stroke; however, the underlying mechanisms are uncertain. In addition, the optimal strategies to prevent and acutely treat stroke in cancer patients are yet to be established.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
188
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(232 citation statements)
references
References 84 publications
(284 reference statements)
6
188
0
20
Order By: Relevance
“…Other potential mechanisms of stroke in cancer disease include nonbacterial endocarditis, paradoxical embolism, tumor embolism, vasculitis, and vascular compression by masses or vessel wall infiltration. Importantly, recurrence rates are high, ranging from 13% to 28%, and correlating with increased D‐dimer levels . A multi‐territory scattering lesion pattern on DWI sequences of brain MRI is more frequently encountered and is representative of the intense microembolism .…”
Section: Cancermentioning
confidence: 99%
“…Other potential mechanisms of stroke in cancer disease include nonbacterial endocarditis, paradoxical embolism, tumor embolism, vasculitis, and vascular compression by masses or vessel wall infiltration. Importantly, recurrence rates are high, ranging from 13% to 28%, and correlating with increased D‐dimer levels . A multi‐territory scattering lesion pattern on DWI sequences of brain MRI is more frequently encountered and is representative of the intense microembolism .…”
Section: Cancermentioning
confidence: 99%
“…5 A Danish registry-based case-control study with over 264 000 cancer patients also showed an approximately 2-fold risk for ischemic stroke in occult cancers. 8 Cancer can also cause marantic (non-bacterial) endocarditis, mechanical compression of critical vessels, anemia, and tumor embolism. However, lung, pancreatic, and colorectal cancers seem to have a higher association with ischemic stroke, perhaps due to their aggressiveness.…”
mentioning
confidence: 99%
“…6 No solid data exist on exact prevalence of different cancer types in ischemic stroke patients. 8,9 Other potential mechanisms that increase the risk of ischemic stroke in the presence of cancer include endothelium dysfunction and abnormalities in turbulence in abnormal blood vessels. 7 Other reported common cancer types include breast, urogenital and prostate cancers.…”
mentioning
confidence: 99%
See 2 more Smart Citations